Hubungan Pengetahuan dan Personal Hygiene Terhadap Kesehatan Reproduksi - Yulia Hariani (Jurnal Kesehatan Abdurrahman, 2022)
Reproductive health is a state of overall health that includes physical, mental and social life related to reproductive organs, functions and processes. Reproductive health greatly determines the fertility of every individual, so it is important for people to get correct and correct information about reproductive health. The results of the 2019 national analysis show that 39.1% of the population in Indonesia practice clean and healthy living behaviors. So that the changes made in 2019 had an impact on achieving a clean and healthy lifestyle index. Efforts to achieve a clean and healthy life behavior index are by implementing health promotion activities with the help of promotional media (pocket books). The purpose of writing this literature review is to determine the relationship between personal hygiene and reproductive health. This study uses the Literature Review method, namely by searching for article data sources taken using Google Scholar, Garuda Portal and Pubmed. The period of the articles used as references is from 2019 - 2021. From the results of the selection that was carried out using the inclusion and exclusion criteria, 10 articles were found to be reviewed. The results obtained from the 10 reviewed articles all state that there is a significant relationship between personal hygiene and reproductive health.